Kontribusi Keterampilan Manajemen terhadap Efektivitas Desa Wisata di Desa Wisata Meat Toba Samosir Sumatera Utara - Erika Revida; Sukarman Purba (Universitas Negeri Medan, 2019)
The aim of this study was to analyze the contribution of management skills on the effectiveness of Meat tourism village. The specific objective of this study was analyzed the contribution of conceptual skills, human relations skills, and technical skills on contributioniveness of Meat tourism village Toba Samosir North Sumatera. The sample of this study were 60 head of family in Meat tourism village. Data collection techniques carried out by documentation studies, research instruments, interviews and observations. The data analysis technique used was multiple regression analysis. The results showed that there was a positive and significant contribution between management skills on the effectiveness of Meat tourism village. There was a positive and significant contribution between conceptual skills on the effectiveness of Meat tourism village, there was a positive and significant contribution between human relations skills on the effectiveness of Meat tourism village, and there is a positive and significant contribution between technical skills on effectiveness of Meat tourism village. The results showed that human relations skills were the dominant contribution followed by conceptual skills and technical skills in Meat tourism village Toba Samosir, North Sumatera.